No preterm relative telomere length shortening in patients on successful cART - Gordana Dragovic; Ena Bukic; Bozana Obradovic; Jovan Ranin; Bosko Toljic; Jelena Jadzic; Jelena Milasin (Journal of Global Antimicrobial Resistance)
AIM: This study aimed to determine whether the duration of human immunodeficiency virus (HIV) infection and combination antiretroviral therapy (cART) affect telomere length (TL) in people living with HIV (PLWHIV). BACKGROUND: Preterm aging caused by accelerated cellular senescence in PLWHIV has become an important issue nowadays. The biomarker of aging that explains the discrepancy between chronological and biological age in PLWHIV is TL. Different factors such as cellular environment, HIV per se, as well as cART may affect TL. METHODS: This matched case-control study was conducted on 176 PLWHIV and 176 HIV-negative controls, all Caucasians, all males. To be eligible for the study patients had to fulfill following criteria: to be on stable cART for at least 12 months, 18 years and older, not to have other chronic or acute infection, have no malignancy, no hepatitis C and hepatitis B virus and no human papilloma virus co-infection, no clinical depression and sleeping disturbance. Relative telomere length (RTL) was determined by Real-time polymerase chain reaction from mononuclear cells. Genomic DNA was isolated from mononuclear cells, relative to a unique reference sequence by salting out method. RESULTS: The mean age was 42.7±13.2 years. The mean RTL was 2.50±1.87. The total duration of HIV infection averaged 92.4±72.2 months. Patients were receiving cART for an average of 82.02±64.81 months. The Kendall correlation test showed that cART do not affect preterm RTL shortening in PLWHIV (p=0.002) with HIVRNA plasma-viral-load below 50 copies/mL. CONCLUSIONS: The timely introduction of successful cART does not affect preterm telomere shortening.